Production of triacetine a plant design - Beltran, Angelo A. (College of Engineering, 1993)
Product: Triacetine -- Description: sp.grav at 20 C = 1.16, density = 9.7 lbs./gal., melting point = -78 C, boiling point = 258 C, without color or odor, a viscous liquid -- Major use: CO absorber in cigarette filters -- Major market: cigarette manufacturers like Fortune Tobacco and Sterling Cigarettes -- Plant location: Sta. Rosa Technopark, Laguna -- Plant capacity: 1,915,750 kg./yr -- Total capital investment: P 33,033,565 -- Net profit: 34,906,714/yr -- Return on investment: 105.67 % -- Pay-back period: 0.55 years -- Break-even point (sales volume): 907,890 kg. -- Break-even point (gross earnings): P 47,089,530